2020
DOI: 10.1101/2020.04.02.020859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypoxia-related radiomics predict immunotherapy response: A multi-cohort study of NSCLC

Abstract: word count: 398 Word count: 4245 Abstract Checkpoint blockade immunotherapy provides improved long-term survival in a subset of advanced stage nonsmall cell lung cancer (NSCLC) patients. However, highly predictive biomarkers of immunotherapy response are unmet clinical need. In this study, we utilized pre-treatment clinical factors and quantitative image-based biomarkers (radiomics) to identify a parsimonious model that predicts survival outcomes among NSCLC patients treated with immunotherapy. The NSCLC patie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…These results are comparable to state-of-the-art methods, which currently employs laborious and time-consuming segmentation procedures (11,12). While the field of research has been focusing on single-lesion analysis-leveraging different known factors in cancer growth, including vascularity (30), oxygenation (31), and metabolic activity (32)-our approach offers a novel fully automatic procedure which completely eradicates the need of timeconsuming segmentations, and simultaneously offers a way to provide a full picture of the patient status as seen on chest imaging. While this does not preclude the usefulness of the single-lesion approach, it proposes a way for future multi-scale solutions that leverage both single lesion imaging biomarkers as well as whole image approaches that provide general quantitative information about the status of the patient receiving treatment.…”
Section: Discussionmentioning
confidence: 56%
“…These results are comparable to state-of-the-art methods, which currently employs laborious and time-consuming segmentation procedures (11,12). While the field of research has been focusing on single-lesion analysis-leveraging different known factors in cancer growth, including vascularity (30), oxygenation (31), and metabolic activity (32)-our approach offers a novel fully automatic procedure which completely eradicates the need of timeconsuming segmentations, and simultaneously offers a way to provide a full picture of the patient status as seen on chest imaging. While this does not preclude the usefulness of the single-lesion approach, it proposes a way for future multi-scale solutions that leverage both single lesion imaging biomarkers as well as whole image approaches that provide general quantitative information about the status of the patient receiving treatment.…”
Section: Discussionmentioning
confidence: 56%
“…Tunali et al. performed genomic analysis and immunohistochemistry analysis for carbonic anhydrase IX, and demonstrated that CT treatment response biomarkers for patients with lung cancer treated with immunotherapy were strongly associated with hypoxia, a prognostic factor ( 56 ). Ganeshan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al(12) utilized PET/CT radiomics of 399 NSCLC patients from a single institute to generate a classifier model with an AUC of 0.86. For the studies utilizing radiomics to predict immunotherapy treatment response, Tunali et al built parsimonious classifier models with pre-treatment CT radiomic features combined with clinical covariates to predict hype-progression and progressive disease phenotypes with AUCs of 0.80-0.87(22), which were also highly correlated with PFS and OS of immunotherapy(23). Trebeschi et al(24) developed a CT-based radiomic signature that significantly discriminated progressive disease from stable and responsive disease (AUC=0.83) among NSCLC patients treated with immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…When the DLS was combined with clinical covariates and tested in two cohorts for clinical utility by identifying patients most like to benefit to immunotherapy, we found high C-indices of 0.83-0.86 for predicting DCB, but somewhat attenuated C-indices of 0.72-0.78 for the DLS to predict PFS and OS. These models also demonstrated good performance in the external VA cohort.While others have demonstrated the utility of radiomics as a non-invasive approach to predict PD-L1 expression(11,12) or predict lung cancer immunotherapy treatment response(22)(23)(24)(25)(26) , the current work is the first to develop a PD-L1 radiomic signature and then to use this for response prediction. With respect to PD-L1 expression prediction, Patil et al (11) utilized CT images from 166 early stage NSCLC patients from a single institution to develop and validate a machine learned predictor of PD-L1 status with an AUC of 0.73.…”
mentioning
confidence: 99%